2022
DOI: 10.3389/fpsyg.2022.938983
|View full text |Cite
|
Sign up to set email alerts
|

How Can Servant Leadership Promote Employees’ Voice Behavior? A Moderated Chain Mediation Model

Abstract: PurposeBased on Social Exchange Theory, this paper constructs and evaluates the mediation model of servant leadership on employees’ voice behavior through psychological security and error learning ability and discusses the moderation role of work autonomy in the model.DesignThis research used 424 employees and their direct superiors as the research objects and then conducted a paired survey at three points. Mplus7.4 software analyzed the empirical data.FindingsThe results are shown servant leadership is positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…Second, our work expands the antecedents of employee voice behaviors by demonstrating how digital leadership influences it. While previous research has identified paternalistic (Nazir et al, 2021) and humble leadership (Chen et al, 2022) as critical factors that impact employee voice behaviors, the advent and development of digital technology have changed how managers and employees communicate, collaborate, and exchange information (Ding et al, 2022). The lack of face-to-face communication and interpersonal interaction may lead to feelings of disconnection and increased psychological distance among employees (Bernauer & Kornau, 2024).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, our work expands the antecedents of employee voice behaviors by demonstrating how digital leadership influences it. While previous research has identified paternalistic (Nazir et al, 2021) and humble leadership (Chen et al, 2022) as critical factors that impact employee voice behaviors, the advent and development of digital technology have changed how managers and employees communicate, collaborate, and exchange information (Ding et al, 2022). The lack of face-to-face communication and interpersonal interaction may lead to feelings of disconnection and increased psychological distance among employees (Bernauer & Kornau, 2024).…”
Section: Discussionmentioning
confidence: 99%
“…As such, they view employee voice behaviors as both a responsibility and an opportunity to contribute to organizational development (Gilstrap & Hart, 2020), offering both prohibitive and promotive voices. Work engagement is an employee’s autonomous, voluntary investment, and when employees invest more, they become more concerned about organizational situations (Chen et al, 2022) to maximize profits and minimize losses (Cook, 2015). Therefore, when digital leadership meets employees’ needs and encourages work engagement, employees are motivated to express their concerns and offer suggestions for improvement through prohibitive and promotive voices (Kao et al, 2022; T.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Positive styles of leadership, such as participative leadership [17], moral leadership [18,19], and servant leadership [13,20], have been shown to have a positive in uence on employees' voice behavior. Affective leadership falls into this category, prioritizing the interpersonal relationship between superiors and subordinates over the authority of leaders [15].…”
Section: Hypothesismentioning
confidence: 99%